TWO CO-INHERITED SNPS OF THE TELOMERASE REVERSE TRANSCRIPTASE (TERT) GENE ARE ASSOCIATED WITH IRAQI PATIENTS WITH LUNG CANCER : association of TERT gene with lung cancer - Lawi, Zahraa K.; Ben Amara, Ibtissem; Alkhammas, Ahmed H.; Elerouri, Malek; Al-Shuhaib, Mohammed Baqur S. (Journal of Medical Biochemistry, 2023)
Background: Telomerase reverse transcriptase (TERT) gene is essential for the survival of the vast majority of malignant tumors. This study was conducted to assess the association between TERT gene and non-small cell lung carcinoma (NSCLC) in Iraq. Methods: Genomic DNA samples were extracted from a total of 200 samples of blood. Four specific PCR fragments were designed to amplify four high-frequency rs2735940, rs2736098, rs2736100, and rs10069690 SNPs within the TERT gene. Single-strand conformation polymorphism (SSCP) followed by sequencing reactions were used to genotype and validate the amplified fragments respectively. Results: Individuals with the genotype rs2735940:A/G had a significantly higher risk of developing NSCLC (P=0.0299; OD 2.3158; Cl95% 1.0853 to 4.9414). Individuals with the genotype rs2736098:C/T had also associated with the increased risk of NSCLC (P=0.0363; OD 2.1583; Cl95% 1.0503 to 4.4351). Linkage disequilibrium analysis showed that both SNPs showed a very high level of coinheritance in patients. The LD plot showed that allele T of rs2736098 had collaborated with allele G of rs2735940 to generate TG haplotype in patients. According to our findings, TERT- rs2735940:A/G and TERT- rs2736098:C/T SNPs exhibited significant associations with the increased risk of NSCLC. Both SNPs showed the highest values of co-inheritance in patients. This co-inheritance is mainly represented by allele rs2735940:A and allele rs2736098:C. Both pathogenic T and G alleles have generated TG haplotype that is only available in patients’ samples. Conclusion: This study suggests employing the haplotype TG as a promising biomarker for the early diagnosis of NSCLC. These findings need further validation by large-scale investigation with a larger size of samples in the study population.